Pengelolaan Sektor Usaha Food And Beverages Oleh Unit Commercial di Terminal Keberangkatan Bandar Udara I Gusti Ngurah Rai Bali - Selvia Egita Barus; Amelia Puspa Tamara (Jurnal Multidisiplin Indonesia, 2023)
The Food and Beverage business sector at the Airport contributes to developing the non-aeronautical economy of PT Angkasa Pura 1 by utilizing the Commercial area and Airport layout which is managed by the Commercial Operation Strategic Business Unit of I Gusti Ngurah Rai Bali Airport and outlet operations are carried out by Business Partners . Supervision and control of business partner outlets is carried out to create appropriate operational conditions. This research was conducted using qualitative research methods, data collection was carried out using interviews, observations, documentation and literature studies in the Commercial area of the Airport departure terminal and in the office of the Commercial Operation Strategic Business Unit at I Gusti Ngurah Rai Airport, Bali. This research was conducted to determine the management carried out by Commercial officers in the Food and Beverage business sector at the Airport departure terminal. The results of this research are that the management carried out by operational officers is running well, this is proven by the performance of officers who carry out daily routine supervision and checks, morning and evening and storage checks at business partner outlets.